THE INTERNATIONAL LEGAL ISSUES OF COMPENSATION FOR THE CRIME OF AGGRESSION UNDER THE MARTIAL LAW AND THE POST-WAR PERIOD - Andreikiv, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the study is to analyze the institutional certainty of international legal mechanisms for compensation for damage for crimes of aggression both during martial law and in the period after its completion, and the possible regulatory regulation of certain gaps in the current regulation and to provide proposals for possible ways to improve the relevant mechanisms of international law. The article, based on a pluralistic methodological toolkit, which includes general scientific and special scientific research methods, explores the distinctive features of international legal mechanisms of compensation, understood as the provision of restitution and monetary redress to individuals whose rights and legitimate interests have been violated as a result of an act of aggression — the gravest breach of international law. Discussion: the analysis underscores that the institution of compensation in international law encompasses financial redress and monetary payments applicable to both public and private legal relations. Particular attention is given to Articles 30 and 31 of the Draft Articles on the Responsibility of States for Internationally Wrongful Acts, developed by the UN International Law Commission, which establish the liability of the aggressor for wrongful conduct, the duty to cease such conduct, and the parallel obligation to provide reparations for the damage inflicted. The article highlights that compensation, as one of the principal forms of reparation alongside restitution, satisfaction, and rehabilitation, constitutes one of the most effective instruments for the restoration of infrastructure objects across different forms of ownership, as well as for the recovery of individual households. Results: it is further emphasized that the development of international legal cooperation aimed at ensuring compliance with compensation obligations requires not only legal mechanisms, but also coordinated engagement of judicial, financial, and law enforcement institutions. The fundamental premise of such cooperation entails the establishment of national reparation programs and complementary assistance to victims in circumstances where the parties responsible for the harm are unable or unwilling to fulfill their obligations.